(untitled) (Revista de História Regional, 2007)
The article analysis the tecno-bureaucratic literature about the city and the population of Curitiba, on the two first decades of the 20th century, with the vision of formulating tactics and procedures of disciplinarization and normalization of the population and the urban environment, with the intention of obtaining its complete governamentalization. Aspects of public order, justice, criminality, and those regarding hygiene, sanitation and public health are here analyzed.